Safe alternatives for treating hypertension and diabetes in older adults of the Federal District - Brazil (Revista Contexto & Saúde, 2025)
Introduction: This study aims to present alternatives available in the Unified Health System for de-prescribing potentially inappropriate drugs (PIM) or potential drug interactions (PDI) in the treatment of hypertension or diabetes mellitus (DM) in the elderly in the Federal District. Methods: A cross-sectional study was carried out with an analysis of prescriptions to identify PIM and an analysis of clinical protocols and guidelines. The aim was to present alternatives from the list of standardized medicines of the Federal District Health Department and the Brazil's Popular Pharmacy Program. Results: The most frequent PIM was insulin (13.7%), followed by clonidine (1.6%) and glibenclamide (1.0%). The most frequent PDI was between angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors or potassium-sparing diuretics (6.6%). Discussion: Antidiabetics with a lower risk of causing hypoglycemia, such as metformin and dapagliflozin, are available from the Federal District Health Department and the Brazil's Popular Pharmacy Program. Modified-release gliclazide is an alternative to sulfonylureas, with advantages in terms of efficacy in glycemic control, cardiovascular safety and low potential for triggering hypoglycemia; however, free access is restricted to the Federal District Health Department. The availability of thiazide diuretics, beta-blockers and calcium channel blockers in the SUS makes it possible to associate antihypertensives that act on the renin-angiotensin system more safely. Conclusion: The differences between the List of Medicines of the State of the Federal District and the Brazil's Popular Pharmacy Program showed that the Federal District Health Department offers more options for treating hypertension or DM, including safer alternatives for older adults and the possibility of more effective drug combinations.
Keywords: deprescriptions; potentially inappropriate medication list; hypertension; diabetes mellitus; aged; access to essential medicines and health technologies